Assessment of Chokeberry Powders Quality Obtained Using an Innovative Fluidized-Bed Jet Milling and Drying Method with Pre-Drying Compared with Convection Drying - Anna Sadowska; Franciszek Świderski; Ewelina Hallmann; Katarzyna Świąder (Foods, 2021)
There is a need and great interest among food producers in obtaining powders from fruit and vegetables of both high nutritional value and sensory qualities superior to those hitherto obtained by convection drying (CD) and spray drying methods and cheaper to prepare than the sublimation method. This study is focused on whether powders can be obtained from fruit berries with a sticky structure, using the chokeberry (Aronia melanocarpa) as a test example, by a combined fluidized-bed jet milling and drying (FBJD) of pre-dried fruit by CD to an adequate water activity (aw). The pre-drying step reduced sticking between fruit particles during the simultaneous drying and grinding processes of the FBJD method in order to obtain powders of desired granulation. Three different pre-drying temperatures of 50, 60, and 70 °C were tested for levels of microorganisms in chokeberries at a water activity of 0.4. Vitamin C content and antioxidant properties were also examined along with polyphenol separation. Fruit pre-dried at 60–70 °C had significantly higher vitamin C and polyphenolic content and greater antioxidant properties than those pre-dried at 50 °C. Further studies were thus undertaken on powders pre-dried at 70 °C in which antioxidant properties, vitamin C, and polyphenols content were also compared with CD obtained powders. The FBJD method combined with CD pre-drying proved superior to just using the CD method, where powders had a greater preservation of vitamin C at 84% (CD powders 35%), a 12% higher total polyphenol content, and a 10% higher antioxidant activity. The test method also uses a much shorter drying time than the CD method, because the grinding of the hard-textured material takes only few minutes.